Evaluation of the Constancy Stake Model for the Implementation of Cleanliness, Health, Safety, and Environment Sustainability (CHSE) Program in Supporting Tourism Health Development in Lovina, Bali - Erawati, Ni Ketut; Sugandini, Wayan; Juliani, Made (Media Publikasi Cendekia Indonesia, 2025)
Lovina is one of the leading tourist destinations in North Bali, which is the target of the CHSE (Cleanliness, Health, Safety, and Environmental Sustainability) program as an effort to realize safe and sustainable tourism. However, there has been no systematic evaluation regarding the implementation of CHSE in the community living in tourist area. Therefore, this study aims to analyze the antecedents (planning), transaction (process), and outcomes (output) of CHSE program. A descriptive approach was used with a Countenance Stake evaluation model including 3 main stages, namely context (planning), process (implementation), and outcomes (output). Furthermore, this study comprised 50 respondents, consisting of the community living around the Lovina tourist area selected using a purposive sampling technique. Data were collected through interviews, questionnaires, and documentation of the local CHSE program. The results showed that the implementation of CHSE program in Lovina has been excellent, although several aspects still need to be improved, including community understanding of standards, active participation in implementing health protocols, and support from the local government, both in the form of ongoing socialization and supervision. At the antecedents stage, 62% of respondents confirmed readiness and understanding of the appropriate category. Meanwhile, at the transaction stage, 60% of respondents routinely implemented hygiene practices according to CHSE guidelines. At the outcomes stage, most respondents (88%) had a perception in accordance with sustainability. In conclusion, this study provides an important contribution to the development of health-based tourism in Bali, specifically emphasizing the importance of collaboration between the government, tourism actors, and the local community. As a recommendation, the results can be used as basis for formulating effective policies in improving the quality of safe, healthy, and sustainable tourism services in the Lovina tourist destination and other areas in Bali.